If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -113 = 7 + 10x Solving -113 = 7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -113 + -10x = 7 + 10x + -10x Combine like terms: 10x + -10x = 0 -113 + -10x = 7 + 0 -113 + -10x = 7 Add '113' to each side of the equation. -113 + 113 + -10x = 7 + 113 Combine like terms: -113 + 113 = 0 0 + -10x = 7 + 113 -10x = 7 + 113 Combine like terms: 7 + 113 = 120 -10x = 120 Divide each side by '-10'. x = -12 Simplifying x = -12
| 7/6x+3x/5 | | 34=16*x-14 | | 6(3+2x)-1=65 | | a+(b^2)*3c-2d= | | (9ab+7cd)*3e= | | r+0.10=760 | | 9ab+7cd= | | 30=-5/4x | | m=19-5(x-n) | | 5a+4b+3c+4d+3e= | | 5a*4b*3c*4d*3e= | | r/2+0.6r=247 | | 2a-3b=12 | | 8-2(t-1)=t+7 | | 5a*4b*3c= | | 7/5+8/3d | | 7=(3x+9)+7 | | A^3+2a-25a-5/a-5 | | 525+0.21m=85 | | 120=w+41 | | -5/6-4/15 | | 525+0.21m=585+0.13m | | 711=q-800 | | A^3+2a-25a-50=0 | | 59+m=258 | | 7-4x= | | 5x-5(9x+11)=25 | | g+720=159 | | 23+b=75 | | .6=.30n | | .6=.3on | | 8x+8(-7-1x)=24 |